Оптимальний розподіл гідроресурсів у зрошувальних системах мережевої структури - Kirik, O. E.; Ostapenko, V. V. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2010)
A mathematical model of transportation and distribution of resources with a generalized conservation law is created. For this optimization problem of flow retention within the given limits, algorithms for efficient nonlinear programming are developed. The proposed approach gives the opportunity to solve problems of flow distribution with multitype nonlinear objective functions for networks with any number of closed loops.